Growing together: A qualitative study of leading nurse scholars in Thailand - Turale S. (2014)
Background: Asia-Pacific nursing education and research is growing but little is known about the nature and development of nursing scholarship in the region. Aim: This qualitative study explored the perspectives of 14 leading Thai scholars about the development, facilitators and barriers relating to Thailand's nursing scholarship. Method: In-depth interviews were digitally recorded, and data were subjected to content analysis. Findings: Five themes arose: (1) growing together, (2) visionary leadership, (3) external support to grow nurse scholars, (4) developing nursing through research, and (5) barriers to scholarship. A history of visionary nursing leadership was revealed, underpinned by leaders' values of growing nursing together. Resource sharing among universities, and a significant number of scholarships for study abroad were major facilitators of scholarship growth. Barriers to scholarship included high teaching loads, especially for newly graduated faculty; a low rate of research publications; not enough mentorship for research and changes to teaching practice; and a wide range of different agencies providing courses for entry to practice. Conclusions: Scholarship development in Thailand is a role model for a number of South-East Asian countries, with inclusiveness and collaboration to facilitate the growth of nursing education inside and outside of the country as a hallmark of its character. However, against a backdrop of nursing shortages, Thai scholars are challenged, in the future, to produce meaningful research outcomes, including publications of studies; to collaborate with other health professionals; change practices to overcome high teaching loads; and provide the much needed mentorship for young scholars. © 2010 The Authors. Journal compilation © 2010 International Council of Nurses.